Cacao consumption improves passive avoidance memory impairment in a rat model of Alzheimer’s disease: the role of hippocampal synaptic plasticity and oxidative stress - Basir, Hamid Shokati; Mirazi, Naser; Komaki, Alireza; Hosseini, Abdolkarim (Frontiers in Pharmacology, 2024)
Alzheimer's disease (AD) causes progressive loss of cognitive function and synaptic plasticity, the most common form of dementia. The present study was designed to scrutinize the effects of cacao on passive avoidance memory function and to identify the roles of hippocampal synaptic plasticity and oxidative stress in an AD rat model induced by unilateral intracerebroventricular (UICV) injection of amyloid-beta (Aβ). Oral administration of cacao (500 mg/kg/day) was given for two consecutive months. A memory retention test was conducted 24 hours after passive avoidance training was completed. Subsequently, the amplitude of population spike (PS) and slope of field excitatory postsynaptic potentials (fEPSP) were assessed at hippocampal long-term potentiation (LTP) in perforant pathway-dentate gyrus (PP-DG) synapses. Moreover, total thiol group (TTG) and malondialdehyde (MDA) concentrations were evaluated in the plasma. Further, compact Aβ plaques were detected in the hippocampal DG by Congo red staining. As a result of AD induction, passive avoidance memory was impaired, as well as reduced fEPSP slopes, PS amplitudes, content of TTG, and increase in MDA levels in the rats were observed. In contrast, cacao treatment ameliorated passive avoidance memory impairment, improved hippocampal LTP impairment, modulated oxidative-antioxidative status, and delayed Aβ plaques production in AD rats. Conclusively, cacao alleviates Aβ-induced cognitive deficit, probably by amelioration of hippocampal LTP impairment, modulation of oxidative-antioxidative status, and inhibition of Aβ plaque accumulation.